Perception of laboratory management and quality improvement concepts of Saudi anatomic pathology residents and graduates: Venues for improvement - Amal A. Alodaini; Nida M. Khan; Zahra F. Alkhunaizy (Journal of Family and Community Medicine)
Abstract: BACKGROUND: Laboratory management and quality improvement (LMQI) is a fundamental nondiagnostic skill for the daily practice of pathologists. Studies recognized a knowledge gap in LMQI in postgraduate training programs with non-uniform outcomes. Measurement of this gap and corrective curricula modifications was embraced by many postgraduate programs. Similar assessment of the LMQI knowledge status in Saudi anatomic pathology (AP) residents and graduates is lacking. The aim of this study was to assess Saudi AP residents’ perceptions of LMQI concepts, and AP graduates’ feedback on the usefulness of LMQI training for their practice as pathologists, and propose a revised LMQI curriculum. MATERIALS AND METHODS: A nonexperimental mixed-methods study was conducted between August 1 to August 31, 2020. An online questionnaire containing multiple-choice and closed-ended questions assessed LMQI learning experiences of AP residents and graduates. A comparative assessment of LMQI curricula was done between Saudi and international AP postgraduate programs as a benchmark. Descriptive statistics were computed to summarize the participants’ demographic characteristics and the surveyed variables using SPSS. RESULTS: A remarkable LMQI knowledge gap was noted at all residency levels, which was mirrored by the graduates’ feedback of difficulties in LMQI issues they were encountering as junior pathologists. The LMQI curricula assessment in Saudi AP programs revealed that the objectives and evaluation methods were vague. A revised competency-driven longitudinal LMQI curriculum with clear expectations and evaluation methods is proposed. CONCLUSION: LMQI as an objective has been translated differently in the current Saudi AP programs with limited experiential LMQI learning resulting in suboptimal and inhomogeneous outcomes. This requires a unified model with longitudinal, competency-based experiential training.